Corporate Governance in Transition Dealing with Financial Distress and Insolvency in UK Companies - Parkinson, Marjan Marandi (Palgrave Studies in Governance, Leadership and Responsibility,, 2018)
This book presents an account of legal, economic and managerial perspectives on governance in situations of financial distress and insolvency. It uses detailed real-life case studies of executive decision making to explore and illustrate the discussion. The book deals with the emergence of corporate governance as a framework of checks and balances on executive decision-making, before moving to the core issues of governance during financial distress and insolvency and alternative informal and formal rescue. Identifying and reviewing turnaround strategies and formal rescue processes available to management, the book also examines the increasing importance of creditors and their impact on business decision-making. The book provides a detailed interpretation of governance in five mega insolvencies in retail and construction following the financial crisis in 2008. It also sets out a methodology which is designed to inform and help those readers seeking to analyse and interpret director behaviour in such circumstances.